Analysis of Elementary School Students' Numeracy Literacy Ability in Solving Minimum Competency Assessment (AKM) Questions: Case Study of Challenges and Opportunities - Putri, Megayanti Hendiana; Kurnia Sari, Nurratri; Suswandari, Meidawati (Universitas Ma'arif Lampung, 2024)
This research was motivated by the phenomenon of implementing the minimum competency assessment (AKM) in class V at SD Negeri 01 in Karanganyar Regency. The researcher discussed in depth the numeracy literacy skills and challenges faced by grade 5 students in working on minimum competency assessment (AKM) mathematics questions at SD Negeri 01 in Karanganyar Regency as well as the opportunities gained from the results of the minimum competency assessment test (AKM) at SD Negeri 01 in Karanganyar Regency. The aim of this research is to 1) describe numeracy literacy and the challenges faced in working on minimum competency assessment (AKM) questions in mathematics for class V students at SD Negeri 01 in Karanganyar Regency, 2) describe the opportunities obtained from the results of the minimum competency assessment test (AKM) mathematics for class V students at SD Negeri 01 in Karanganyar Regency. This research method uses qualitative research using a case study approach. MThe results of this research show: 1) numeracy literacy skills are still low. This is proven by the average score of the Minimum Competency Assessment (AKM) test results, which is 28.24 out of a total of 17 students. The challenges faced are that students are using laptops for the first time in the test, students still cannot understand the questions in the AKM test, students are still difficulty in determining the formula used to solve the problem, and the material that has been taught by the teacher is still not well understood, 2) the opportunity for the Basic Competency Assessment (AKM) test can be used as an evaluation for teachers in making learning improvements for students to improve their abilities numeracy literacy. This implies improving the learning process, increasing evaluation and measurement as well as individual intervention and support for students.